Earnings Growth of Mexican Immigrants: New versus Traditional Destinations - Neeraj Kaushal; Ce Shang (Institute for the Study of Labor (IZA), 2013)
We study the earnings of Mexican immigrants in their traditional and newer destinations in the US. Analysis based on longitudinal data suggests that during 2001-2009, the real wage of Mexican immigrants increased 1-2% a year at the traditional destinations, but remained mostly statistically insignificant at the newer destinations. Mexicans at the traditional destinations exhibited greater residential stability: internal migration, non-follow up in the longitudinal data, and predicted return migration were higher among immigrants at the newer destinations than among immigrants at the traditional destinations. Predicted return migration was found to be selective on past earnings among men, but not among women. For men, a 10 percentage point increase in predicted probability of return migration was associated with a 0.3-0.5% lower wage in the year prior to return.
Keywords: J61; J15; 330; Mexican immigrants; selection; earning assimilation; geographic dispersion; return migration